2018
DOI: 10.1139/cjps-2018-0019
|View full text |Cite
|
Sign up to set email alerts
|

The profitability of diverse crop rotations and other cultural methods that reduce wild oat (Avena fatua)

Abstract: With the increasing resistance of wild oat (Avena fatua L.) to herbicides, there is a need to evaluate the potential of alternative cropping systems based on integrated weed management principles. A 5-yr field study at eight sites across Canada was used to evaluate the profitability of alternative cropping systems that have the potential to control wild oat using cultural practices in conjunction with herbicides. Cultural practices included twice the recommended seeding rates, fall-seeded winter crops, barley … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In this study, we identified that crop rotation with 3 yr of an alfalfa crop (flax-barley-alfalfa-alfalfa-alfalfa-flax) was the most consistent in managing both A. fatua and G. spurium with reduced herbicides over the long term. However, alfalfa may not be attractive for grain growers due to a reduction in cash flow during the 3 yr the alfalfa is grown (Smith et al 2018), unless there is a demand for hay the region. Nevertheless, our results show it can have a marked impact on weed populations before growing flax, a crop for which few herbicide options exist.…”
Section: Indian Headmentioning
confidence: 99%
“…In this study, we identified that crop rotation with 3 yr of an alfalfa crop (flax-barley-alfalfa-alfalfa-alfalfa-flax) was the most consistent in managing both A. fatua and G. spurium with reduced herbicides over the long term. However, alfalfa may not be attractive for grain growers due to a reduction in cash flow during the 3 yr the alfalfa is grown (Smith et al 2018), unless there is a demand for hay the region. Nevertheless, our results show it can have a marked impact on weed populations before growing flax, a crop for which few herbicide options exist.…”
Section: Indian Headmentioning
confidence: 99%
“…Many also incorporate unplanned biodiversity, by preserving some wild elements or natural areas within the farm, or attracting various species to planned elements (e.g., hedgerows). Such practices nurture biodiversity below ground, helping farmers build soil health, which directly supports crop growth while improving resilience to disease, drought, and floods (Gaudin et al, 2013;Poeplau and Don, 2015;Smith et al, 2018;Weisberger et al, 2019;Archer et al, 2020;Bowles et al, 2020;Wade et al, 2020). At the same time, enhancing biodiversity on the farm promotes aboveground services like pollination and pest control by providing habitat for pollinators, beneficial insects, and other wildlife (Kremen and Miles, 2012;Morandin et al, 2016;Garratt et al, 2017;Dainese et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Farmers have known for millennia that planting the same crop in the same field year after year quickly leads to impoverished soil and unmanageable populations of disease organisms, weeds, and insect pests (Bullock, 1992;Howieson et al, 2000;Karlen et al, 2006). Similarly, recent studies have demonstrated that increasing the diversity of a simple crop rotation by even a few crops can result in not only similar or greater overall crop productivity and economic returns compared to the conventional rotation, but also improved soil fertility and lower pest populations and lower requirements for fertilizer and pesticide inputs (Smith et al, 2008(Smith et al, , 2018Davis et al, 2012;Weisberger et al, 2019;Archer et al, 2020). What is more, numerous studies have shown that the ecosystem services that arise from diversifying crop rotations, such as soil quality and fertility enhancements, can also help buffer these systems against weather variability associated with climate change (Bommarco et al, 2013;Gaudin et al, 2015;Williams et al, 2016;Bowles et al, 2020).…”
Section: Introductionmentioning
confidence: 99%